2019
DOI: 10.1103/physrevb.99.180404
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of spin transparency by interfacial alloying

Abstract: We report that atomic-layer alloying (intermixing) at a Pt/Co interface can increase, by approximately 30%, rather than degrade the interfacial spin transparency, and thereby strengthen the efficiency of the dampinglike spin-orbit torque arising from the spin Hall effect in the Pt. At the same time, this interfacial alloying substantially reduces fieldlike spin-orbit torque. Insertion of an ultrathin magnetic alloy layer at heavy-metal/ferromagnet interfaces represents an effective approach for improving inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
88
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 37 publications
5
88
0
Order By: Relevance
“…The decrease of T int with K s is less likely to suggest a decrease in HM/FM ⇵ here because previous studies have indicated that magnetic roughness (e.g. induced by diffusion) may increase T int via moderately enhancing HM/FM ⇵ [42,43]. Finally, while processes (iii) and (iv) that should increase DL E are still possisible, they seem to be a weaker effect than the SML process as indicated by the decrease of T int with enhancing K s .…”
Section: Influence Of Short-wavelength Magnons On Spin Torquementioning
confidence: 96%
“…The decrease of T int with K s is less likely to suggest a decrease in HM/FM ⇵ here because previous studies have indicated that magnetic roughness (e.g. induced by diffusion) may increase T int via moderately enhancing HM/FM ⇵ [42,43]. Finally, while processes (iii) and (iv) that should increase DL E are still possisible, they seem to be a weaker effect than the SML process as indicated by the decrease of T int with enhancing K s .…”
Section: Influence Of Short-wavelength Magnons On Spin Torquementioning
confidence: 96%
“…In contrast, two-magnon scattering (TMS) [29,30] predominantly determines the tFM dependence of α. When ISOC is sufficiently strong, the second largest contribution can be spin memory loss (SML) [12,[31][32][33][34][35]. Neglecting TMS and SML, particularly the former, when analyzing measurements of α in HM/FM systems gives unphysical "giant" estimates for eff ↑↓ and hence incorrect quantification of spin-dependent transport phenomena across HM/FM interfaces and large errors in the determination of θSH and σSH.…”
mentioning
confidence: 99%
“…Note that the drift-diffusion model [4,17] and Eq. (1) [12,[31][32][33][34][35] provides an additional spin sink that can increase α and degrade Tint for the HM/FM interface. However, we find that the giant eff, ↑↓ values are not due primarily to SML.…”
mentioning
confidence: 99%
“…20,[28][29][30] Recent studies suggesting that measurements of the SHA may actually be dominated by interface effects 20,28,31,32 are stimulating attempts to tailor these. [33][34][35][36][37] This makes it crucial to have a way to independently determine interface parameters. We recently described a formalism to evaluate local charge and spin currents 8 from the solutions of fully relativistic quantum mechanical scattering calculations 38 that include temperatureinduced lattice and spin disorder.…”
mentioning
confidence: 99%